APLIKASI AIR MINUM TERAPI ORGANIK PADA ORGANIK AL-BAROQAH BERBASIS WEB - Lisdarti - (JURNAL AKADEMIKA)
To facilitate and maintain a business mest have the qualitty of good work and structured, information is very important to facilitate promotion media in business activities trade. Organic Al-baroqah is a business entity engaged in selling organic therapy drinking water. In Organic Al-baroqah operational process by means of directly communicate based on the agrement, marketing system is still in manual by using the distribution of brochures and selling limited only several areas in Jambi city. Therefore, the writer want to build an application that would facilitate buyers and explain the details product and can do the activities selling through the internet that is an aplication based on WEB prgrame. The website also can be used as a means to expand the marketing areas out oof Jambi city. The writer build this application is using PHP and MySQL as aplace of data stroge. Using this application Organic Al-baroqah can be easier for giving information to their customers especially out of jambi’s city that will affect the sales increase and costumer’s loyalityt to Organic Al-baroqah Jambi.